PENGELOLAAN DANA KELURAHAN DALAM PENINGKATAN PEMBERDAYAAN MASYARAKAT DAN SARANA DAN PRASARANA DI KELURAHAN WONOASIH KECAMATAN WONOASIH KOTA PROBOLINGGO - Cahyaningtyas, Niken Triwahyuni; Natsir, Mohammad (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2024)
This research aims to determine the effectiveness of sub-district fund management and determine the supporting and inhibiting factors for sub-district fund management in wonoasih Village, Wonoasih District, Probolinggo City. The results of the Qualitative research that has been carried out show that in the management of sub-district funds in Wonoasih Sub-district there are still several factors that can hinder the realization of the budget so that its absorption is not optimal, besides that there is no continuity of several community empowerment activities that have been implemented so that the program objectives are not achieved. It is hoped that these obstacles can be minimized and regulated in the new Mayor’s Regulations which are currently still in the drafting stage.